1993
DOI: 10.1073/pnas.90.8.3740
|View full text |Cite
|
Sign up to set email alerts
|

Activated estrogen receptor mediates growth arrest and differentiation of a neuroblastoma cell line.

Abstract: Several reports demonstrate estrogen receptor involvement in specific brain functions. In addition, estrogen receptors are expressed at early stages of brain development, suggesting that estrogens or related molecules may play an instructive role in the differentiation of specific brain areas. The lack of model systems in which these phenomena could be studied prompted us to develop a neuroblastoma cell line expressing the estrogen receptor. The cell line expresses the hormone receptor at levels compatible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 33 publications
4
56
0
Order By: Relevance
“…Our demonstration of ESR1 expression in human fetal sympathetic ganglia suggests that ESR1 plays an important role during the development of the sympathetic nervous system. Furthermore, ESR1 has been reported to induce growth arrest and differentiation of NB cells following estradiol treatment (27). Our data support this finding, as we observed ESR1-mediated neuronal differentiation of SK-N-BE(2) cells.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our demonstration of ESR1 expression in human fetal sympathetic ganglia suggests that ESR1 plays an important role during the development of the sympathetic nervous system. Furthermore, ESR1 has been reported to induce growth arrest and differentiation of NB cells following estradiol treatment (27). Our data support this finding, as we observed ESR1-mediated neuronal differentiation of SK-N-BE(2) cells.…”
Section: Discussionsupporting
confidence: 82%
“…Next, we analyzed the functional role of ESR1 expression in NB cells. Even though it is well-established that ESR1-mediated signaling contributes to proliferation of breast cancer cells (26), it has been reported that ligand-dependent activation of ESR1 in neuronal cells results in growth arrest and differentiation (27). To reaffirm this finding, we used lentiviral constructs expressing ESR1 cDNA and transduced SK-N-BE(2) cells.…”
Section: Esr1 Is Repressed By Mycn-induced Mirnas and Contributes Tomentioning
confidence: 99%
“…Diminished or absent ER expression has been associated tightly with methylation of a CpG island in the ER promoter in multiple cell types; Methylation of the ER gene has previously been seen in 100% of colon cancers (Issa et al, 1994), 80% of leukemias (Issa et al, 1996c), 25% of lung cancers (Issa et al, 1996a) and 25% of ER negative breast cancers (Lapidus et al, 1996). Reexpression of ER inhibits cell growth in various cancer cell lines including breast (Zajchowski et al, 1993;Jiang and Jordan, 1992), colon (Issa et al, 1994), neuroblastoma (Ma et al, 1993) and HeLa cells (Maminta et al, 1991). Our present data suggest that ER methylation (and presumed loss of expression) may play a role in the pathogenesis of GBMs as well.…”
Section: Discussionsupporting
confidence: 54%
“…ER is expressed in normal brain and its transcript has been detected in di erent types of cultured glial cells (Santagati et al, 1994). Recent studies of ER in several tumor types have indicated that this molecule may have tumor suppressor properties (Ma et al, 1993;Garcia et al, 1992). Diminished or absent ER expression has been associated tightly with methylation of a CpG island in the ER promoter in multiple cell types; Methylation of the ER gene has previously been seen in 100% of colon cancers (Issa et al, 1994), 80% of leukemias (Issa et al, 1996c), 25% of lung cancers (Issa et al, 1996a) and 25% of ER negative breast cancers (Lapidus et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The data accumulated so far prove that E 2 can induce these cells to cease proliferation and to accumulate in the G 0 phase of the cell cycle, acquiring the phenotype of a mature dopaminergic neuron (Agrati et al, 1997). We also proved that several of the activities attributed to E 2 in vivo can be reproduced in our model, i.e., induction of the synthesis of specific proteins, including c-Fos, synaptophysin, and tau, or modulation of neurite growth (Ma et al, 1993;Santagati et al, 1995). We therefore believe that SK-ER3 cells represent a unique system for the study of E 2 action in neural cells.…”
mentioning
confidence: 59%